Sosialisasi Peran Orang Tua di Kelurahan Mudung Laut dalam Memanfaatkan Aplikasi Google Family untuk Keamanan Anak dalam Bermain Media Sosial - rahmayanty, dinny; Carissa Eka Lisviona; Dini Apriliani Natasha; M. Dwiki Ramadha; Shelly Marcelina Nababan; Tri Wahyu Ningsih (Universitas Garut, 2025)
The rapid development of technology and social media has positive and negative impacts on children. In facing these challenges, parents have an important role in supervising and guiding children to use social media safely. This study aims to analyze the role of parents in Mudung Laut Village in utilizing the Google Family application as a digital supervision tool to improve children's safety in playing social media. This study uses a qualitative descriptive approach with interview and observation methods of a number of parents who use the Google Family application. The results of the study show that most parents in Mudung Laut Village have started using this application to limit gadget usage time, monitor children's online activities, and filter content that can be accessed. However, there are still several obstacles faced, such as the lack of digital literacy among parents and children's resistance to digital supervision which is considered to limit their freedom. This study concludes that the use of Google Family can be an effective solution in improving children's safety when playing social media, as long as it is supported by technology education for parents and open and persuasive communication patterns between parents and children.